Associations between cord blood metabolic factors and early-childhood growth and overweight and obesity - Jin, Wen-Yuan; Chen, Xiao-Yang; Han, Ting; Jin, Yan; Chen, Ting-Ting; Wang, Zi-Han; Zhao, Zheng-Yan; Zhu, Zhi-Wei (Frontiers in Endocrinology, 2023)
Objective: This prospective cohort study was aimed at investigating the associations between cord blood metabolic factors and early-childhood growth, further elucidating the relationships between cord blood metabolites and overweight and obesity in early life. Methods: A total of 2267 pairs of mothers and offsprings were recruited in our study. Cord blood plasma was assayed for triglycerides (TG), total cholesterol (TC), low-density lipoprotein-cholesterol (LDL-C), high-density lipoprotein-cholesterol (HDL-C), C-peptide, insulin and glycosylated hemoglobin, type A1C (HbA1c) levels. Data of anthropometric measurements were collected from offsprings at birth, 6 months, 12 months and 18 months. Multiple linear regression models were used to evaluate the correlations between cord blood metabolic factors and weight Z-scores, body mass index (BMI) Z-scores and weight gains at early stage of life. Forward stepwise logistic regression analyses were applied to explore the associations between cord blood metabolic factors and early-childhood overweight and obesity. ROC curve analyses were applied to determine the optimal cutoff points for cord blood metabolic factors in predicting early-childhood overweight and obesity. Results: After adjustments for covariates, cord blood TG concentrations and TG/TC ratios were negatively associated with weight Z-scores from birth to 18 months. Cord blood C-peptide and HbA1c levels were inversely associated with weight Z-scores at 6 months and 18 months. Cord blood TG concentrations and TG/TC ratios were negatively correlated with BMI Z-scores up to 18 months. Cord blood C-peptide levels and HbA1c levels were inversely correlated with BMI Z-scores at 18 months. Cord blood TG, TG/TC ratios, C-peptide and HbA1c had negative correlations with weight gains from birth to 6 months, but the correlations attenuated as time went on. Increase in cord blood TG, HbA1c levels and TG/TC ratios were significantly associated with decreased risks of overweight and obesity at 6 months, 12 months and 18 months. Conclusions: Cord blood metabolic factors were significantly associated with early-childhood growth patterns.